The Influence of Professional Habits on Performance Efficiency and Error Prevention in Nursing Practice (2019–2024) - Shimran, Hasanain Yhiya; Aljesham, Amenah Abd Al Hassan Jebur (Journal of Science in Medicine and Life, 2025)
In the medical field, the job of a nurse entails undertaking many important tasks without indulging into too many mistakes. If nurses create strong habits that can be triggered by their surroundings, their goals are much easier to achieve. Between 2019 and 2024 studies have shown that developing good habits can help improve productivity workflow in nursing and reduce mistakes. It helps you to suggest ways to encourage a healthy habit and useful ways to stop or lessen a bad habit.